Ceramic green body and ceramic tile free of binder and raw slime and preparation method of ceramic green body and ceramic tile

By adopting ceramic body formulas without binders and raw ore mud, and using multi-stage differentiation screening and spray granulation processes, the dependence on high-quality raw ore mud and lithium tailings in ceramic production is solved, and ceramic body production with high whiteness, low carbon content and environmental benefits is achieved.

CN119551976AActive Publication Date: 2025-03-04JIANGXI WONDERFUL CERAMICS CO LTD +3
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411748934.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-04
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

In the production of existing ceramics, high-quality raw ore mud and lithium tailings after secondary lithium extraction are difficult to effectively utilize, resulting in high production costs and environmental pollution, and the products are prone to defects such as black hearts, pores and surface pinholes.

Method used

The ceramic body formula without binder and raw ore mud is mainly composed of ultrafine lithium tailing sand, zero-strength lithium tailing sand, yellow field sand and talc. Through multi-stage differentiation sieve and spray granulation technology, fiber impurities in the lithium tailing sand are removed to achieve high whiteness and low carbon content of the blank.

Benefits of technology

The high whiteness (25°) and low carbon content (0.07~0.08%) of the ceramic blank are achieved, which avoids black hearts, reduces production costs, improves the density of the product and surface anti-fouling performance, and has significant environmental benefits.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a ceramic green body and a ceramic tile which do not contain a binder and raw slime and a preparation method of the ceramic green body and the ceramic tile. The ceramic body without the binder and the raw slime is further prepared from the following components in parts by weight: 55 parts of superfine lithium tailings, 20 parts of zero-strength lithium tailings, 15 parts of yellow field sand and 10 parts of talc; corresponding chemical components are composed of the following components in percentage by weight: 4.07% of LOI, 25.50% of SiO2, 17.43% of Al2O3, 0.16% of Fe2O3, 0.06% of CaO, 2.57% of MgO, 0.03% of K2O, 0.04% of Na2O and 0.14% of Li2O. The preparation method comprises the following steps: (1) ball-milling and pulping; (2) performing multi-stage differentiation sieving, homogenizing and aging; (3) performing spray granulation to obtain powder; (4) compression molding; (5) performing surface decoration; (6) high-temperature firing is conducted, the highest firing temperature ranges from 1050 DEG C to 1110 DEG C, and the firing time ranges from 45 min to 60 min.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic production, and particularly relates to a ceramic body and a ceramic brick free of binder and raw ore mud, and a preparation method thereof. Background Art

[0002] Clay raw materials are one of the three major raw materials in building ceramics. They are sticky and plastic, and play the role of bonding ridge raw materials. At the same time, they also play a decisive role in the whiteness and strength of the green body. Based on cost considerations, raw ore mud is generally used as clay raw materials in building ceramic raw materials. Although raw ore mud and clay are both muddy substances in nature, raw ore mud is unprocessed natural mud with more complex composition. At the same time, as a non-renewable resource, especially high-quality raw ore mud such as black mud with good whiteness, low iron content and good strength and plasticity, the existing stock has been declining year by year with the previous large-scale mining, and the price remains high. Due to the shortage of high-quality raw materials, the quality of the raw materials currently mined continues to decline. In addition to the decrease in plasticity, the content of organic matter and impurities has also increased, and the chemical composition fluctuates greatly. Some raw ore mud even needs to be washed with water after mining to filter out impurities to meet the basic use requirements, which causes serious pollution to the environment. This processing method is not sustainable today with increasing environmental pressure.

[0003] In actual production activities, compared with barren raw materials and flux raw materials, raw ore mud clay raw materials have high organic matter content, large burning loss, large burning shrinkage, and are prone to increase the amount of body pores and surface pinholes, resulting in reduced product density and surface anti-fouling performance, and difficult to control the flatness of the brick surface. Especially for low-quality raw ore mud, as the organic matter content increases, if the oxidation time of the firing stage is shortened blindly just to avoid defects caused by organic matter in the raw materials, the product will be in a raw state and the product performance will not meet the standards. If the oxidation time of the firing stage is extended, it will not only increase the firing time and production costs accordingly, but also reduce production capacity, which is contrary to the low-temperature fast firing technology requirements currently promoted by the industry.

[0004] Of course, there are also ceramic reinforcing agent auxiliary materials that replace part of the original ore mud. This can reduce the difficulty of purchasing the original ore mud to a certain extent and reduce the problem of product sandwiching, but its production cost is high and it is not widely used. In addition, some companies use bentonite to replace part of the original ore mud, but the disadvantage is that the performance of bentonite slurry is poor and it is difficult to debond. In order to ensure the performance of the mud during ball milling, more water is often needed, resulting in a large amount of water in the slurry out of the ball, most of which are greater than 35%, or even above 37%, which has a great impact on the bulk density quality of the product powder in the later spray drying process and the energy consumption of the drying tower.

[0005] On the other hand, Yichun, as the lithium capital of Asia, has the world's largest lithium mica mine, and produces about 75 million tons of waste each year from lithium extraction. These wastes have greatly restricted the development of lithium extraction companies. This is mainly because the tailings after secondary lithium extraction usually contain a variety of impurities (especially various fibrous impurities) and residual lithium compounds, which may have certain chemical activity. These substances will continue to react under specific conditions. For example, due to the physical and chemical treatment of the lithium extraction process, the particle size distribution of the tailings changes. During use, some particles may become more active due to the reaction, while other particles may gather together to form larger particles. It is precisely because most of the lithium tailings after secondary lithium extraction are too fine and contain too many various fibrous impurities and have low strength. In addition, the kaolin component is added to improve the plasticity and sintering strength of the product. During the firing process, the lithium tailings that are ball-milled again are mixed with kaolin, which is not well oxidized and the product is easy to be black-hearted. The elongated oxidation zone not only fails to increase the kiln speed, but also easily causes bulging and surface pinhole defects. Therefore, lithium tailings after secondary lithium extraction are rarely used in the formula of ceramic tile bodies, and even if used, only a small amount is dared to be added.

[0006] Under the heavy pressure of environmental protection and corporate production costs, how to use other raw materials to replace production has become a consensus in the industry. On the one hand, high-quality raw mud ore is scarce and expensive, and it is hard to come by. On the other hand, the large amount of tailings formed by secondary lithium extraction has caused tremendous pressure on the environment and lithium extraction companies. Therefore, how to effectively utilize mining waste resources while reducing ecological pollution is an urgent problem that needs to be solved. Summary of the invention

[0007] In view of the shortcomings of the above-mentioned prior art, the technical problem solved by the present invention is to provide a formula with a carbon content of only 0.07-0.08%, without the black heart phenomenon, and the whiteness of the green body after firing can reach 25°, which is 5-6° whiter than the current conventional 20° green body, and can fully meet the whiteness requirements of the green body in production. At the same time, the green body formula does not contain a binder, nor does it use bentonite, so there is no need to consider the high cost of auxiliary materials and the performance of bentonite slurry. The ceramic green body does not contain binders and raw ore mud. Another technical problem solved by the present invention is to provide a formula that uses a large amount of lithium tailings formed after secondary lithium extraction, which is low in cost and is most conducive to saving high-quality ceramic raw material resources and promoting the development of the ceramic industry. The technical problem solved by the present invention is to provide a ceramic green body that does not contain binders and raw ore mud and performs multi-level differentiation screening on the green body mud to remove various fiber impurities contained in the lithium tailings after secondary lithium extraction, avoid bulging or surface pinhole defects in the process of product preparation, and use ceramic green bodies that do not contain binders and raw ore mud to prepare ceramic bricks and their preparation methods.

[0008] The technical solution of the present invention is the ceramic body without binder and raw ore mud, which is special in that it is composed of the following components by weight: 55-65 parts of ultrafine lithium tailings, 10-20 parts of zero-strength lithium tailings, 12-18 parts of Huangtian sand, and 8-12 parts of talc; the corresponding chemical composition is composed of the following components by weight percentage: LOI 3.79-5.57%, SiO2 69.81-76.37%, Al2O3 16.54-18.84%, Fe2O3 0.14-0.57%, CaO 0.05-0.45%, MgO 2.17-3.58%, K2O 0.02-0.52%, Na2O 0.04-0.56%, and Li2O 0.14-0.25%.

[0009] Preferably, the ceramic body is further composed of the following components by weight: 55 parts of ultrafine lithium tailings, 20 parts of zero-strength lithium tailings, 15 parts of Huangtian sand, and 10 parts of talc; the corresponding chemical components are composed of the following components by weight percentage: LOI 4.07%, SiO2 75.50%, Al2O3 17.43%, Fe2O3 0.16%, CaO 0.06%, MgO 2.57%, K2O0.03%, Na2O 0.04%, and Li2O 0.14%.

[0010] Preferably, the ultrafine lithium tailings are lithium tailings with finer particles formed after secondary lithium extraction and relatively stable chemical composition after multiple homogenization, and the particle size distribution is: D10=2.43μm, D25=6.01μm, D50=13.89μm, D75=29.49μm, D90=49.69μm; the particle fineness is 10-15% on the 325 mesh sieve, the strength is between 2.0 and 2.2MPa, and the whiteness is 25-27°. The chemical composition corresponding to the ultrafine lithium tailings is composed of the following components by weight percentage: LOI 3.87%, SiO2 70.12%, Al2O3 17.43%, Fe2O3 0.73%, CaO 0.43%, MgO 1.77%, K2O 1.9%, Na2O 3.5%, and Li2O 0.25%.

[0011] Preferably, the zero-strength lithium tailings are lithium tailings with slightly coarse particles formed after secondary lithium extraction and relatively stable chemical composition after multiple homogenization, and the particle size distribution is: D10=2.79μm, D25=8.15μm, D50=20.19μm, D75=39.17μm, D90=58.33μm; the particle fineness is 18-25% on the 325 mesh sieve, the strength is 0, and the whiteness is 75-78°. The chemical composition corresponding to the zero-strength lithium tailings is composed of the following components by weight percentage: LOI 0.83%, SiO278.48%, Al2O3 12.78%, Fe2O3 0.12%, CaO 0.35%, MgO 0.11%, K2O 2.2%, Na2O 4.96%, and Li2O 0.17%.

[0012] Preferably, the Huangtian sand is an aluminous sand with an aluminum content of >20%, which plays a skeleton role in the formula, has a whiteness of 70-73°, and a strength of 1.8-2.2 MPa; the chemical composition corresponding to the Huangtian sand is composed of the following components by weight percentage: LOI 7.83%, SiO2 68.83%, Al2O3 21.78%, Fe2O3 0.38%, CaO 0.17%, MgO 0.11%, K2O0.7%, and Na2O 0.2%.

[0013] Preferably, the chemical composition of the talc consists of the following components by weight: LOI 6.03%, SiO2 58.24%, Al2O3 10.08%, Fe2O3 1.47%, CaO 0.53%, MgO 23.01%, K2O 0.23%, and Na2O 0.41%.

[0014] Another technical solution of the present invention is the method for preparing ceramic tiles without binder and raw ore mud, which is special in that it includes the following steps:

[0015] ⑴ Ball milling;

[0016] ⑵Multi-level differentiation, screening, homogenization and aging;

[0017] ⑶ Spray granulation, the powder obtained: moisture 6.8-7.3%, bulk density: 0.88-0.9g / ml, particle size distribution: 20 mesh: ≤2%, 40 mesh: 50±5%, 60 mesh: 70-78%, 80 mesh: 97-97.5%, 100 mesh: ≤3%;

[0018] (4) Pressing and forming, punching speed: 6.5-8.3 times / minute, maximum pressure of main cylinder: 36.5-38.5MPa;

[0019] ⑸ Carry out surface decoration, including base glaze, inkjet printing and top glaze;

[0020] (6) High temperature firing, the maximum firing temperature is 1050~1110℃, and the firing time is 45~60min.

[0021] As preferred: the step (1) further comprises:

[0022] (1.1) Pre-grinding and slurrying the ultrafine lithium tailings, weighing the ultrafine lithium tailings and putting them into a single ball mill, adding 36% water for ball milling, according to the characteristics of the ultrafine lithium tailings that the particles are fine and easy to agglomerate, in order to prevent the ultrafine lithium tailings from agglomerating and wrapping the ball stones during the slurrying process and failing to play the role of pre-grinding and slurrying, the ball mill is mainly composed of Φ40 balls, and the slurry is discharged after 10 to 15 minutes, and the slurry is passed through a 40-mesh sieve while the slurry is discharged to remove obvious impurities mixed in the ultrafine lithium tailings, and the ultrafine lithium tailings slurry after sieving enters a stirring tank;

[0023] (1.2) Weigh zero-strength lithium tailings, Huangtian sand and talc according to the formula, convert the ultrafine lithium tailings slurry into the formula ratio using a flow meter, add 15-20% water, add them together in a continuous ball mill for ball milling, and ball mill to a fineness of 1.6-2.0% of the residue on a 325-mesh sieve, and release the slurry, and control the specific gravity at 1.70-1.73.

[0024] As a preference: the step (2) further comprises:

[0025] (2.1) Perform primary screening, and the slurry coming out of the ball mill is screened through a 60-mesh screen while being discharged, and then enters the primary homogenization tank. In order to prevent the precipitation of fine particles in the slurry and better present the impurities in the slurry, the stirring speed of the stirrer in the primary homogenization tank is 6 rpm, and the homogenization and aging are carried out for 12 hours;

[0026] (2.2) Perform secondary screening, and the slurry coming out of the primary homogenizing tank is screened through a double-layer screen, with the upper screen being 80 mesh and the lower screen being 90 mesh, and then enters the secondary homogenizing tank for homogenization and aging for 12 hours;

[0027] (2.3) Perform three-stage screening, and the slurry coming out of the secondary homogenization tank is screened through a double-layer screen, with the upper screen being 100 mesh and the lower screen being 120 mesh, and then enters the third-stage homogenization tank for homogenization and aging for 4 hours;

[0028] (2.4) Perform four-stage screening, and screen the slurry coming out of the three-stage homogenization tank with 120 mesh, and then send it to the spray tower slurry pipeline after screening.

[0029] Another technical solution of the present invention is a ceramic tile without binder and raw ore mud, which is special in that it is prepared by any of the above-mentioned preparation methods.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The ceramic body formula designed by the present invention does not contain binders and raw ore mud, and is doped with a large amount of lithium tailings formed after secondary lithium extraction, which can greatly reduce the use of ordinary raw ore mud materials in ceramic production, solve the industry's dependence on raw ore mud, and realize the continuous production of ceramic tiles at 1050-1100°C. The carbon content in the formula is only 0.07-0.08%, and there will be no black heart phenomenon. The whiteness of the body after firing can reach 25°, which is 5-6° whiter than the current conventional 20° body, and can fully meet the production requirements for the whiteness of the body, with extremely high economic and environmental benefits.

[0032] (2) The present invention utilizes the characteristics of ultrafine lithium tailings and Huangtian sand raw materials with high flexural strength. Through the application in the blank, zero addition of raw ore mud and binder materials in the blank is achieved, and there is no need to consider the high cost of auxiliary materials and the performance of bentonite slurry. The problem of excessive sintering temperature and black core caused by excessive introduction of clay in the ceramic production process is solved.

[0033] ⑶ The present invention removes fibrous impurities in the lithium tailings raw materials after secondary lithium extraction by performing a multi-stage differentiation and screening process on the mud, solves the problems of pores and bulging caused by the introduction of lithium tailings, and thus realizes the industrial application of lithium tailings after secondary lithium extraction.

[0034] (4) Since organic impurities are difficult to be ground finely during the ball milling process, in order to separate the organic impurities in the lithium tailings after the secondary lithium extraction, the present invention grinds the mud finer, grinds the ceramic green body mud without a binder and raw ore mud to a fineness of 1.6-2.0% on a 325-mesh sieve, while the fineness of the conventional green body mud is only 2.6-3.5% on a 325-mesh sieve, distinguishes the mud and the organic impurities, and then performs sieving separation, which can effectively separate the organic impurities in the lithium tailings after the secondary lithium extraction, and avoids defects such as holes and bulging in subsequent processes.

[0035] (5) The present invention screens out substantially all the impurities contained in the lithium tailings formed after the secondary lithium extraction by multi-stage differentiation and screening, thereby achieving a carbon content of 0.07-0.08% in the formula, and no black core will be produced during the high-temperature firing process, and the whiteness of the single-fired green body can reach 24-26°. DETAILED DESCRIPTION

[0036] The present invention will be further described in detail below in conjunction with embodiments:

[0037] The ceramic body does not contain a binder and raw ore mud, and is composed of the following components by weight: 55 parts of ultrafine lithium tailings, 20 parts of zero-strength lithium tailings, 15 parts of Huangtian sand, and 10 parts of talc; the corresponding chemical components are composed of the following components by weight percentage: LOI 4.07%, SiO2 75.50%, Al2O3 17.43%, Fe2O3 0.16%, CaO 0.06%, MgO 2.57%, K2O0.03%, Na2O 0.04%, and Li2O 0.14%.

[0038] The ultrafine lithium tailings are lithium tailings with finer particles formed after secondary lithium extraction and relatively stable chemical composition after multiple homogenization, and the particle size distribution is: D10=2.43μm, D25=6.01μm, D50=13.89μm, D75=29.49μm, D90=49.69μm; the particle fineness is 13% on the 325 mesh sieve (much smaller than the normal original ore mud particle fineness of 40-50% on the 325 mesh sieve), the strength is 2.2MPa, the whiteness is 25°, and the chemical composition corresponding to the ultrafine lithium tailings is composed of the following components by weight percentage: LOI 3.87%, SiO2 70.12%, Al2O3 17.43%, Fe2O3 0.73%, CaO0.43%, MgO 1.77%, K2O 1.9%, Na2O 3.5%, Li2O 0.25%.

[0039] The zero-strength lithium tailings are lithium tailings with slightly coarse particles formed after secondary lithium extraction and relatively stable chemical composition after multiple homogenization, and the particle size distribution is: D10 = 2.79 μm, D25 = 8.15 μm, D50 = 20.19 μm, D75 = 39.17 μm, D90 = 58.33 μm; the particle fineness is 25% on the 325 mesh sieve (smaller than the normal original ore mud particle fineness of 40-50% on the 325 mesh sieve), the strength is 0, the whiteness is 75°, and the chemical composition corresponding to the zero-strength lithium tailings is composed of the following components by weight percentage: LOI 0.83%, SiO2 78.48%, Al2O3 12.78%, Fe2O3 0.12%, CaO 0.35%, MgO0.11%, K2O 2.2%, Na2O 4.96%, Li2O 0.17%.

[0040] The Huangtian sand is an aluminum sand with an aluminum content of >20%, which plays a skeleton role in the formula, with a whiteness of 71° and a strength of 2.2MPa. The chemical composition corresponding to the Huangtian sand is composed of the following components by weight percentage: LOI 7.83%, SiO268.83%, Al2O3 21.78%, Fe2O3 0.38%, CaO 0.17%, MgO 0.11%, K2O 0.7%, and Na2O 0.2%.

[0041] The chemical composition of the talc consists of the following components by weight: LOI 6.03%, SiO2 58.24%, Al2O3 10.08%, Fe2O3 1.47%, CaO 0.53%, MgO 23.01%, K2O 0.23%, and Na2O 0.41%.

[0042] The method for preparing ceramic tiles without binder and raw ore mud comprises the following steps:

[0043] ⑴ Ball milling;

[0044] (1.1) Pre-grinding and slurrying the ultrafine lithium tailings, weighing the ultrafine lithium tailings and putting them into a single ball mill, adding 36% water for ball milling, according to the characteristics of the ultrafine lithium tailings that the particles are fine and easy to agglomerate, in order to prevent the ultrafine lithium tailings from agglomerating and wrapping the ball stones during the slurrying process and failing to play the role of pre-grinding and slurrying, the ball mill is mainly composed of Φ40 ball stones, and the slurry is discharged after 12 minutes of ball milling, and the slurry is passed through a 40-mesh sieve while the slurry is discharged to remove obvious impurities mixed in the ultrafine lithium tailings, and the ultrafine lithium tailings slurry after sieving enters a stirring tank;

[0045] (1.2) Weigh zero-strength lithium tailings, Huangtian sand and talc according to the formula, convert the ultrafine lithium tailings slurry into the formula ratio using a flow meter, add 18% water, add them together in a continuous ball mill for ball milling, and ball mill to a fineness of 1.8±0.1% on a 325-mesh sieve, and release the slurry, and control the specific gravity at 1.71-1.72.

[0046] ⑵Multi-level differentiation, screening, homogenization and aging;

[0047] (2.1) Perform primary screening, and the slurry coming out of the ball mill is screened through a 60-mesh screen while being discharged, and then enters the primary homogenization tank. In order to prevent the precipitation of fine particles in the slurry and better present the impurities in the slurry, the stirring speed of the stirrer in the primary homogenization tank is 6 rpm, and the homogenization and aging are carried out for 12 hours;

[0048] (2.2) Perform secondary screening, and the slurry coming out of the primary homogenizing tank is screened through a double-layer screen, with the upper screen being 80 mesh and the lower screen being 90 mesh, and then enters the secondary homogenizing tank for homogenization and aging for 12 hours;

[0049] (2.3) Perform three-stage screening, and the slurry coming out of the secondary homogenization tank is screened through a double-layer screen, with the upper screen being 100 mesh and the lower screen being 120 mesh, and then enters the third-stage homogenization tank for homogenization and aging for 4 hours;

[0050] (2.4) Performing four-stage screening, the slurry coming out of the third-stage homogenization tank is screened with 120 mesh and then sent to the spray tower slurry pipeline after screening;

[0051] ⑶ Spray granulation, the obtained powder: moisture 7.0±0.1%, bulk density: 0.9g / ml, particle grading: 20 mesh: ≤2%, 40 mesh: 50±5%, 60 mesh: 74-78%, 80 mesh: 97-97.5%, 100 mesh: ≤3%;

[0052] ⑷ Pressing and forming, punching speed 6.5 times / minute, maximum pressure of main cylinder: 38.5MPa;

[0053] ⑸ Carry out surface decoration, including base glaze, inkjet printing and top glaze;

[0054] ⑹ High temperature firing, the maximum firing temperature is 1080℃, and the firing time is 55min.

[0055] The ceramic bricks without binder and raw ore mud are prepared by any of the above-mentioned preparation methods.

[0056] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should fall within the scope of the claims of the present invention.

Claims

1. A ceramic body without binder and raw ore mud, characterized in that: The invention is composed of the following components by weight: 55-65 parts of ultrafine lithium tailings, 10-20 parts of zero-strength lithium tailings, 12-18 parts of Huangtian sand, and 8-12 parts of talc; and the corresponding chemical composition is composed of the following components by weight percentage: LOI 3.79-5.57%, SiO2 69.81-76.37%, Al2O3 16.54-18.84%, Fe2O3 0.14-0.57%, CaO 0.05-0.45%, MgO 2.17-3.58%, K2O 0.02-0.52%, Na2O 0.04-0.56%, and Li2O 0.14-0.25%.

2. The ceramic body without binder and raw ore mud according to claim 1, characterized in that: The ceramic body is further composed of the following components by weight: 55 parts of ultrafine lithium tailings, 20 parts of zero-strength lithium tailings, 15 parts of Huangtian sand, and 10 parts of talc; the corresponding chemical components are composed of the following components by weight percentage: LOI 4.07%, SiO2 75.50%, Al2O3 17.43%, Fe2O3 0.16%, CaO 0.06%, MgO 2.57%, K2O 0.03%, Na2O 0.04%, and Li2O 0.14%.

3. The ceramic body without binder and raw ore mud according to claim 1 or 2, characterized in that: The ultrafine lithium tailings are lithium tailings with finer particles formed after secondary lithium extraction and relatively stable chemical composition after multiple homogenization, and the particle size distribution is: D10=2.43μm, D25=6.01μm, D50=13.89μm, D75=29.49μm, D90=49.69μm; the particle fineness is 10-15% of the residue on the 325 mesh sieve, the strength is between 2.0 and 2.2MPa, and the whiteness is 25-27°. The chemical composition corresponding to the ultrafine lithium tailings is composed of the following components by weight percentage: LOI 3.87%, SiO2 70.12%, Al2O3 17.43%, Fe2O3 0.73%, CaO 0.43%, MgO 1.77%, K2O 1.9%, Na2O 3.5%, and Li2O 0.25%.

4. The ceramic body without binder and raw ore mud according to claim 1 or 2, characterized in that: The zero-strength lithium tailings are lithium tailings with slightly coarse particles formed after secondary lithium extraction and relatively stable chemical composition after multiple homogenization, and the particle size distribution is: D10 = 2.79 μm, D25 = 8.15 μm, D50 = 20.19 μm, D75 = 39.17 μm, D90 = 58.33 μm; the particle fineness is 18-25% of the residue on the 325 mesh sieve, the strength is 0, and the whiteness is 75-78°. The chemical composition corresponding to the zero-strength lithium tailings is composed of the following components by weight percentage: LOI 0.83%, SiO2 78.48%, Al2O3 12.78%, Fe2O30.12%, CaO 0.35%, MgO 0.11%, K2O 2.2%, Na2O 4.96%, and Li2O 0.17%.

5. The ceramic body without binder and raw ore mud according to claim 1 or 2, characterized in that: The Huangtian sand is an aluminum sand with an aluminum content of more than 20%, which plays a skeleton role in the formula, has a whiteness of 70-73°, and a strength of 1.8-2.2MPa; The chemical composition corresponding to the Huangtian sand consists of the following components by weight percentage: LOI 7.83%, SiO2 68.83%, Al2O3 21.78%, Fe2O3 0.38%, CaO 0.17%, MgO 0.11%, K2O 0.7%, and Na2O 0.2%.

6. The ceramic body without binder and raw ore mud according to claim 1 or 2, characterized in that: The chemical composition of the talc consists of the following components by weight: LOI 6.03%, SiO2 58.24%, Al2O3 10.08%, Fe2O3 1.47%, CaO 0.53%, MgO 23.01%, K2O 0.23%, and Na2O 0.41%.

7. A method for preparing ceramic tiles without binder and raw ore mud, characterized in that: The following steps are involved: ⑴ Ball milling; ⑵Multi-level differentiation, screening, homogenization and aging; ⑶ Spray granulation, the powder obtained: moisture 6.8-7.3%, bulk density: 0.88-0.9g / ml, particle size distribution: 20 mesh: ≤2%, 40 mesh: 50±5%, 60 mesh: 70-78%, 80 mesh: 97-97.5%, 100 mesh: ≤3%; (4) Pressing and forming, punching speed: 6.5-8.3 times / minute, maximum pressure of main cylinder: 36.5-38.5MPa; ⑸ Carry out surface decoration, including base glaze, inkjet printing and top glaze; (6) High temperature firing, the maximum firing temperature is 1050~1110℃, and the firing time is 45~60min.

8. The method for preparing ceramic tiles without binder and raw ore mud according to claim 7, characterized in that: The step (1) further comprises: (1.1) Pre-grinding and slurrying the ultrafine lithium tailings, weighing the ultrafine lithium tailings and putting them into a single ball mill, adding 36% water for ball milling, according to the characteristics of the ultrafine lithium tailings that the particles are fine and easy to agglomerate, in order to prevent the ultrafine lithium tailings from agglomerating and wrapping the ball stones during the slurrying process and failing to play the role of pre-grinding and slurrying, the ball mill is mainly composed of Φ40 balls, and the slurry is discharged after 10 to 15 minutes, and the slurry is passed through a 40-mesh sieve while the slurry is discharged to remove obvious impurities mixed in the ultrafine lithium tailings, and the ultrafine lithium tailings slurry after sieving enters a stirring tank; (1.2) Weigh zero-strength lithium tailings, Huangtian sand and talc according to the formula, convert the ultrafine lithium tailings slurry into the formula ratio using a flow meter, add 15-20% water, add them together in a continuous ball mill for ball milling, and ball mill to a fineness of 1.6-2.0% of the residue on a 325-mesh sieve, and release the slurry, and control the specific gravity at 1.70-1.

73.

9. The method for preparing ceramic tiles without binder and raw ore mud according to claim 7, characterized in that: The step (2) further comprises: (2.1) Perform primary screening, and the slurry coming out of the ball mill is screened through a 60-mesh screen while being discharged, and then enters the primary homogenization tank. In order to prevent the precipitation of fine particles in the slurry and better present the impurities in the slurry, the stirring speed of the stirrer in the primary homogenization tank is 6 rpm, and the homogenization and aging are carried out for 12 hours; (2.2) Perform secondary screening, and the slurry coming out of the primary homogenizing tank is screened through a double-layer screen, with the upper screen being 80 mesh and the lower screen being 90 mesh, and then enters the secondary homogenizing tank for homogenization and aging for 12 hours; (2.3) Perform three-stage screening, and the slurry coming out of the secondary homogenization tank is screened through a double-layer screen, with the upper screen being 100 mesh and the lower screen being 120 mesh, and then enters the third-stage homogenization tank for homogenization and aging for 4 hours; (2.4) Perform four-stage screening, and screen the slurry coming out of the three-stage homogenization tank with 120 mesh, and then send it to the spray tower slurry pipeline after screening.

10. A ceramic tile free of binder and raw ore mud, prepared by the preparation method according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Treatment method of superfine weakly magnetic lithium ore tail mud

    CN114870986A

  • Ceramic green body, ceramic tile and preparation method of ceramic green body

    CN115893978A

  • Ceramic blank based on lithium tailings, ceramic tile and preparation method of ceramic blank

    CN118771853A

  • AU2021103189A4